Elaboration of Aged Liquor with National Cocoa Almonds (Theobroma cacao L.) residual from the export classification - Fernández Escobar, Ángel Oliverio (2021)
The objective of this research was to evaluate the effect of the maceration of national cocoa almond residues in rectified ethyl alcohol to obtain old liquor. The cocoa was used roasted and unroasted, and, in different concentrations, added to the 96.19 °GL rectified ethyl alcohol contained in glass bottles set at 4 L and left in maceration for 6 months; The aged liquor was reduced to 25 ± 1 °GL with a fraction of water and another of sucrose syrup of 62.2 °Brix and the sensory evaluation was carried out considering the attributes of color, odor, cocoa flavor and preference. A bifactorial design was applied completely at random, with 3 repetitions. The SPSS statistical software was used, and the Friedman test. From the ADEVA, the T2 corresponding to roasted national cocoa and in a quantity of 500 g was established as the best treatment.